Dispositional honesty-humility and moral disengagement in explaining gossip: does ethical leadership make any difference? - Relvas, Catarina Almeida Isidro (2019)
Moral disengagement occurs when an individual's self-regulatory function is not activated, allowing them to dissociate from the consequences resulting from their behaviors, becoming more prone to make unethical decisions - e.g. gossip about coworkers. It is known that personality is a predictor of Moral disengagement. The Honesty-Humility personality trait, which represents an individual's tendency to be fair and sincere, opposition Moral disengagement processes. Finally, Ethical Leadership also emerges as a deterrent since, through social learning, individuals behave as their ethical leader, avoiding the occurrence of unethical behaviors. It is yet unknown how both interact and if an unethical leadership is able to override the personality deterrent effect. Therefore, the present study aims to find out if Moral disengagement mediates the (negative) relationship between Honesty-Humility and Gossip. Additionally, we try to understand if Ethical Leadership has a moderating role between Honesty-Humility and Moral disengagement - also with a negative relationship between them. With a sample of 358 employees, findings showed that Honesty-Humility is negatively correlated with Moral disengagement and that this relationship is positively moderated by Ethical Leadership. Finally, this study also allowed us to conclude that Moral disengagement mediates the negative relationship between Honesty-Humility and Gossip (only in the case of instrumental gossip) as well as Ethical Leadership positively moderates this relationship.